Local-scale feedbacks influencing cold-water coral growth and subsequent reef formation - Corbera, Guillem; Lo Iacono, Claudio; Simarro, Gonzalo; Grinyó, Jordi; Ambroso, Stefano; Huvenne, Veerle A.I.; Mienis, Furu; Carreiro-Silva, Marina; Martins, Inês; Mano, Beatriz; Orejas, Covadonga; Larsson, Anna I.; et al. (Scientific Reports, 2022)
14 pages, 6 figures.-- Data availability: Data available from the Zenodo Digital Repository: https://doi.org/10.5281/zenodo.6773359 Despite cold-water coral (CWC) reefs being considered biodiversity hotspots, very little is known about the main processes driving their morphological development. Indeed, there is a considerable knowledge gap in quantitative experimental studies that help understand the interaction between reef morphology, near-bed hydrodynamics, coral growth, and (food) particle transport processes. In the present study, we performed a 2-month long flume experiment in which living coral nubbins were placed on a reef patch to determine the effect of a unidirectional flow on the growth and physiological condition of Lophelia pertusa. Measurements revealed how the presence of coral framework increased current speed and turbulence above the frontal part of the reef patch, while conditions immediately behind it were characterised by an almost stagnant flow and reduced turbulence. Owing to the higher current speeds that likely promoted a higher food encounter rate and intake of ions involved in the calcification process, the coral nubbins located on the upstream part of the reef presented a significantly enhanced average growth and a lower expression of stress-related enzymes than the downstream ones. Yet, further experiments would be needed to fully quantify how the variations in water hydrodynamics modify particle encounter and ion intake rates by coral nubbins located in different parts of a reef, and how such discrepancies may ultimately affect coral growth. Nonetheless, the results acquired here denote that a reef influenced by a unidirectional water flow would grow into the current: a pattern of reef development that coincides with that of actual coral reefs located in similar water flow settings. Ultimately, the results of this study suggest that at the local scale coral reef morphology has a direct effect on coral growth thus, indicating that the spatial patterns of living CWC colonies in reef ...